Global Financial Crisis and Islamic Capital Market Integration among 5-ASEAN Countries - Ibnu Qizam; Abdul Qoyum; Misnen Ardiansyah (Global Review of Islamic Economics and Business, 2015)
Islamic Capital Market is important part of Financial System in ASEAN countries especially in the context of AEC. The objective of this paper is to investigate interconnection long run equilibrium of Islamic Capital Market in ASEAN Countries. Using daily closing price for from September 2007 to October 2012, this study examine five Islamic Capital markets in ASEAN namely Indonesia, Malaysia, Philippines, Singapore and Thailand. This study examines on Integration among these Islamic Capital markets by relies a simple correlation test, Granger causality test and co-integration test using error correction model. This research documents some interesting finding. First, Using Johansen estimation technique, there is co-integration between the considered Islamic indices namely; Indonesia, Malaysia, Philippines, Singapore and Thailand. Second, Since the co-integration exists, granger causality test shows that there is three bi-directional causalities namely; between Malaysia Islamic Capital Market and Singapore Islamic Capital Market; between Thailand Islamic Capital Market and Singapore Islamic Capital Market; and between Singapore Islamic Capital Market and Philippines Islamic Capital Market. However, there is a unidirectional between Indonesia Islamic Market (MCIINA) and Malaysia Islamic Market (MCIMY), MCIINA and Philippines Islamic Market (MCIPhil), MCIINA and Thailand Islamic Market (MCITHAI), it implies that MCIINA affects MCIMY, MCIPhil, and MCIThai but not vice versa. Third, based on VECM suggest that all Islamic indexes are inter-related in the long run that can be explained due to the similarity of structure bring about by its stock as required by shariah in the process stock screening.